External Conflict In It Happened One Summer Novel By Tessa Bailey - Sukma, Ni Wayan Cahyani; Putra, I Gde Agoes Caskara Surya (Denpasar Institute, 2024)
The objective of this study is to examine the nature of the conflicts experienced by the main character in Tessa Bailey’s novel It Happened One Summer, with a particular focus on external conflicts. Using a qualitative approach, the data was analyzed and presented descriptively based on established literary theories to provide an in-depth understanding of the character's struggles. Data collection involved a thorough reading of the novel, combined with observation and note-taking to identify significant instances of conflict. Through thematic analysis, the study identified two primary types of conflict: internal and external. External conflict, the more dominant type, includes obstacles and challenges in the character's interactions with other people and the outside world. Internal conflict, by contrast, deals with the character's inner emotional and psychological struggles. These findings highlight the complex interplay between the character's external pressures